Use of Emergency Medical Services in the Second Gulf Registry of Acute Coronary Events. (September 2014) - AlHabib, Khalid F.; Alfaleh, Hussam; Hersi, Ahmad; Kashour, Tarek; Alsheikh-Ali, Alawi A.; Suwaidi, Jassim Al; Sulaiman, Kadhim; Saif , Shukri Al; Almahmeed, Wael; Asaad, Nidal; Amin, Haitham; Al-Motarreb, Ahmed; et al.
Data are scarce regarding emergency medical service (EMS) usage by patients with acute coronary syndrome (ACS) in the Arabian Gulf region. This 9-month in-hospital prospective ACS registry was conducted in Arabian Gulf countries, with 30-day and 1-year follow-up mortality rates. Of 5184 patients with ACS, 1293 (25%) arrived at the hospital by EMS. The EMS group (vs non-EMS) was more likely to be male, have cardiac arrest on presentation, be current or exsmokers, and have moderate or severe left ventricular dysfunction and ST-segment elevation myocardial infarction (STEMI). The EMS group had higher crude mortality rates during hospitalization and after hospital discharge but not after adjustment for clinical factors and treatments. The EMSs are underused in the Arabian Gulf region. Short- and long-term mortality rates in patients with ACS are similar between those who used and did not use EMS. Quality improvement in the EMS infrastructure and establishment of integrated STEMI networks are urgently needed.